Sexual harassment in public spaces towards Peruvian adolescents - Cinthia Rosales Márquez; Andrea Ángela Medina Valverde; Ericson Felix Castillo Saavedra; Cecilia Elizabeth Reyes Alfaro; Raúl Fernando Cruzado Ubillús (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2022)
Background: Public spaces should be safe places for the free movement of people, especially for women, and even more so if they are minors. In the case of adolescent girls, they are often victims of sexual harassment in the streets or other places, a situation that could significantly affect their comprehensive development. Objective: to characterize sexual harassment in public spaces towards Peruvian adolescents. Methods: comparative descriptive study, which included 372 schoolchildren from two educational institutions (one public and one private) in the province of Santa (Peru). The street sexual harassment questionnaire, a 13-item instrument, was applied. Descriptive statistics were used to determine the levels of sexual harassment; while the inferential statistics identified a statistical difference in bullying with respect to both educational institutions. Based on the normality of the data, the Student´s t-test was used. Results: sexual harassment was at a medium level in both schools, 52.4 % in the private one and 45% in the public one. A significant statistical difference was evidenced between the participants of one and another educational center, with respect to the behavioral dimensions of social interaction, verbal component and physical component; as well as sexual harassment in general. Conclusion: Sexual harassment in public spaces was, in most cases, medium level. Social interaction behaviors, as well as the verbal component, were the most prevalent dimensions of bullying towards adolescents from both educational institutions in the province of Santa (Peru).